El control interno y su influencia en la toma de decisiones en la mancomunidad de tránsito del cantón La Maná período 2021. - Miño Soplín, Colón Eduardo (2023)
The purpose of this research work is to evaluate internal control and its influence on decision making in the Mobility Company of the Commonwealth of Cotopaxi Canton La Maná, Province of Cotopaxi in 2021, managing to generate the improvement of the company and the achievement of its objectives. The research that was carried out is of an applied and descriptive type, which allowed improvement strategies, solving problems that exist within the company and analyzing and interpreting data obtained, observing the development of activities and situations at present to promote a possible solution. In order to achieve the objectives or goals of the investigation. Relevant information on the problem in the company was collected, through techniques such as internal control questionnaire. Through the 5 components of COSO I such as: control environment, risk assessment, control activity, information and communication, supervision and monitoring, a confidence level rating of 93% was obtained and the risk level is one. 7%, it was identified that the level of confidence in decision making is high with 93% when proposing procedures, the internal control of each of the activities and their functions can be improved helping to achieve the desired goals, it will be improved through the SWOT. Finally, we proceeded to the elaboration of the proposal of a manual of functions and procedures in the different areas that the entity has, such as: management, accounting, and human talent, in addition, the conclusions and recommendations that have been reached in the investigation.